Beneficial Bacteria Affect Danio rerio Development by the Modulation of Maternal Factors Involved in Autophagic, Apoptotic and Dorsalizing Processes - Miccoli, Andrea; Gioacchini, Giorgia; Maradonna, Francesca; Benato, Francesca; Skobo, Tatjana; Carnevali, Oliana (Cellular physiology and biochemistry, 2015)
Background/Aims: Probiotic strains have been recognized to exert important roles in many biological systems, including immune response, growth, development and reproduction. However, to date, no studies have focused either on the relation among probiotics and maternal factors or on probiotics' ability to qualitatively and/or quantitatively modulate maternal transcripts. Methods: In this study, the effects of Lactobacillusrhamnosus administered to parental fish on the control of maternal factors involved in autophagic, apoptotic and dorsalizing processes during zebrafish embryo development were assessed through q-PCRs, WMISH and TUNEL assay. Results: The results we obtained show that probiotic induced significant changes in both maternal and zygotic mRNA levels involved in embryo development. The maternal autophagy-regulating genes herein investigated -ambra1a, ambra1b, beclin, lc3-, as well as those involved in the apoptotic process -caspase3, bcl2, bax- were modulated in disfavor and favor of the treated group, respectively. Also, the key transcripts ruling the dorsalizing process -goosecoid and chordin- were subject to a significant regulation of their gene expression. Conclusion: The results we acquired demonstrated that parentally administered Lactobacillusrhamnosus is able to modulate important physiological processes involved in zebrafish embryo development.